Undernutrition and associated factors among lactating mothers in Chiro district, eastern Ethiopia: a community-based cross-sectional study - Fekadu, Mesfin; Egata, Gudina; Mengestie, Bezatu; Adem, Hassen Abdi; Usso, Ahmedin Aliyi (Frontiers in Global Women's Health, 2024)
BackgroundMaternal undernutrition during lactation is a worldwide public health problem. It causes impaired cognitive ability, poor productivity, irreversible loss, and intergenerational malnutrition, which has harmful effects on the next generation. Overall, there is little information on undernutrition and risk factors among lactating mothers, especially in resource-poor settings, including Ethiopia. This study assessed undernutrition and associated factors among lactating mothers in rural Chiro district, eastern Ethiopia.MethodA community-based cross-sectional study was conducted among 629 lactating mothers in the Chiro district from July 2–30, 2019. Data were collected from participants using pretested, structured questionnaires and anthropometric measurements. Data were entered using EpiData version 3.1 and analyzed using SPSS version 27. Multivariable logistic regression analyses were used to identify factors associated with undernutrition.ResultsUndernutrition among lactating mothers was 26.9% (95% CI: 23.2%, 30.2%). Female-headed household (AOR = 0.34, 95% CI:0.13, 0.94), medium (AOR = 0.58, 95% CI: 0.38, 0.95) and rich (AOR = 0.30, 95% CI: 0.18, 0.51) wealth quintiles, lack of dietary advice (AOR = 1.62, 95% CI: 1.10, 2.39), chewing khat (AOR = 1.82, 95% CI: 1.23, 2.70), low dietary diversity (AOR = 3.10, 95% CI: 1.82, 5.29), and household food insecurity (AOR = 3.67, 95% CI:1.47, 9.20) were factors significantly associated with undernutrition.ConclusionsAround one in every four lactating mothers in rural eastern Ethiopia had undernutrition. Poor wealth, lack of dietary feeding advice, substance use disorder, low minimum dietary diversity, and household food insecurity were factors significantly associated with the undernutrition of lactating mothers. Thus, focusing on implementing existing strategies/programs for effective nutritional interventions and poverty alleviation that enhance food security status would be essential to improving the nutritional status of lactating mothers and children.